Antimicrobial screening of endophytic fungi isolated from the aerial parts of Paepalanthus chiquitensis (Eriocaulaceae) led to the isolation of secondary metabolites produced by Fusarium fujikuroi - Hilário, Felipe [UNESP]; Chapla, Vanessa M. [UNESP]; Araujo, Angela R. [UNESP]; Sano, Paulo T.; Bauab, Taís M. [UNESP]; Dos Santos, Lourdes C. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2017)
The screening for antimicrobial activity of twenty five endophytic fungi isolated from the aerial parts of Paepalanthus chiquitensis (Eriocaulaceae) was assayed against the bacteria Gram-positive Staphylococcus aureus, Gram-negative Escherichia coli and Salmonella setubal, and the yeast fluconazole-resistant Candida albicans. The ethyl acetate extract produced by Fusarium fujikuroi was the most bioactive and this fungus was chosen for the chemical study, affording the isolation of an alkaloid 2-(4-butylpicolinamide) acetic acid and three known metabolites: fusaric acid, indole acetic acid and the sesterterpene terpestacin. The minimal inhibitory concentration of the extract and of fusaric acid and indole acetic acid for all the tested microorganisms had values from 125 to 1000 µg mL-1.
Keywords: Antimicrobial activity; Endophytic fungi; Fusarium fujikuroi; Paepalanthus chiquitensis